Kontribusi Usaha Ternak Sapi Perah Terhadap Pendapatan Keluarga Peternak di Kecamatan Musuk Kabupaten Boyolali - Sutrisno Hadi Purnomo; Endang Tri Rahayu; Aris Adik Setyawan (Universitas Sebelas Maret (UNS), 2015)
The purpose of this study was to determine the characteristics and management of dairy cattlebusiness, analyze the contribution of dairy cattle business to the family income of farmers, analyze therelationship between business income dairy cattle farm and revenue contribution of dairy cattle,analyze the influence of various factors on the level of production the income of farmers. This researchwas conducted in the Ringin larik village, Kebun Gulo and Dragan at District Musuk of BoyolaliRegency in July 2013. The method is Rapid Rural Appraisal (RRA). Total of sample of 60 respondents.The data is primary data from interviews of respondents and secondary data obtained from relevantagencies in the district boyolali. Analysis of the data used is descriptive analysis, analysis of revenuedairy farmers, ranchers analysis of household income, revenue contribution analysis of dairy cattleranchers on household income, pearson correlation analysis and multiple linear regression analysis.The results showed an average responden net income of the business dairy cattle 4 scale isRp. 6,483,050.33 in year. The contribution of business dairy cattle breeders to household income is19,38%. The correlation of value between the scale of the dairy cattle business with revenues andcontribution of dairy cattle income has a positive value is 0,597 and 0,521. Positive values indicatethat larger scale dairy cattle business will increase farmers income and have a strong relationship.The results of the t test on regression analysis, coefficient of t hitung variable labor costs (X3) and thecost of IB (X5) is 2,081 and 2,066 greater or significant t tabel.